Technology sovereignty as an emerging frame for innovation policy: Defining rationales, ends and means - Jakob Edler; Knut Blind; Henning Kroll; Torben Schubert (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2021)
In recent years, global technology-based competition has not only intensified, but become increasingly linked to a more comprehensive type of competition between different political and value systems. Against this background, the notion of technology sovereignty has gained prominence in national and international debates as an additional rationale for innovation policy, cutting across the established perspectives or paradigms of economic competitiveness and socio-technical transformation. In this paper, we propose and justify a concise yet nuanced concept of technology sovereignty to contribute to and clarify this debate. We offer a balanced perspective of a nation's legitimate interest in ascertaining the availability of and access to technologies on the one hand, and the dangers posed by autarky and protectionism on the other hand, which are detrimental to global trade and eventually welfare. In contrast to much of the initial policy discourse, we derive our concept from economic and sociological theories. In particular, we argue that technology sovereignty should be conceived as state-level agency within the international system, i.e. as sovereignty of governmental action, rather than (territorial) sovereignty over something. Against this background, we define technological sovereignty not as an end in itself, but as a means to achieve the central objectives of innovation policy - sustaining national competitiveness and building capacities for transformative policies. Based on this motivation, future policies will have to aim at establishing a stable, albeit dynamic, equilibrium between sovereignty and openness. To accomplish this, we propose three types of policies. First, new forms of strategic intelligence and foresight will be essential to understand the need for action to secure technology sovereignty and how to achieve it. Second, we propose to mobilise a set of traditional STI policies that have specific importance in the context of technology sovereignty, such as investing in research and the development of competences and high-level infrastructure as well as supporting entrepreneurial activities in emerging technologies, demand-side policies to establish technological lead markets, and international scientific and technological cooperation. Third, we propose a set of policies specifically targeted at securing technology sovereignty, such as international standardisation, strong regulatory frameworks, complementary competition, trade and investment policies and strengthening international institutions to safeguard rule-based trade and competition. We conclude by highlighting a number of challenges stemming from the political economy dynamics that are to be expected should technology sovereignty become a leading rationale for innovation policy.
urn:nbn:de:0011-n-6383436
Keywords: 330; Technologiepolitik; Technologie; Souveränität; Autarkie; Internationaler Wettbewerb; Neue politische Ökonomie